Lifestyle of Office Employees at the Primary Clinic Secretariat Building of the Supreme Court of the Republic of Indonesia - Fera Ferianti; Omega DR Tahun (Budapest International Research and Critics University, 2023)
Hypertension is a disease that affects many people in developing countries, such as Indonesia. This disease has become a threat to many people because of an unhealthy lifestyle. Hypertension is a strong and important risk factor for cardiovascular and kidney diseases, such as coronary disease, heart failure and kidney failure. The purpose of this study was to determine the relationship between lifestyle and the incidence of hypertension in office employees at the Primary Clinic Secretariat Building of the Supreme Court of the Republic of Indonesia. This type of research is analytic quantitative with a cross-sectional study design. The sample selection technique was carried out by means of non-probability sampling, and the type of statistical test used was chi square. The population in this study were all employees who visited the Primary Clinic of the Court Secretariat Building, the sample size was 87 respondents. Statistical test results showed that the factor associated with the incidence of hypertension was diet (p value = 0.019; OR =3,143), exercise habits (p value=0.048; OR=2,647), and stress level (p value=0.040; OR=2,742). While the factor that is not related to hypertension is smoking behavior (p value = 0.523; OR =1,467). To all employees to control blood pressure so they don't suffer from hypertension by: avoiding salty and fast food, exercising regularly and reducing stress when carrying out work in the office.